HUBUNGAN IMPLEMENTASI PROGRAM DANA DESA UNTUK KETAHANAN PANGAN DENGAN PERSEPSI MASYARAKAT MENGENAI TERCAPAINYA SUSTAINABLE DEVELOPMENT GOALS (SDGs) DESA - Fitri , Yanuar; Wahyuni, Ira; Andriani, Iis (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2024)
The Village Fund Program launched in recent years has yielded varying impacts across rural areas in Indonesia. One of the measurable indicators of its effectiveness is the contribution toward achieving the Sustainable Development Goals (SDGs) at the village level. This study aims to (1) identify and understand the village fund programme in the food security sector, (2) examine the implementation of the programme, and (3) analyse the relationship between the implementation of the village fund programme for food security and community perceptions regarding the achievement of Village SDG 2 (Zero Hunger). A purposive sampling method was used to select beneficiaries of the food security program in Gunung Labu Village (Kayu Aro Barat Sub-district), Hamparan Pugu Village (Air Hangat Barat Sub-district), and Talang Kemulun Village (Danau Kerinci Sub-district). The research employed a quantitative approach with an observational design. The results show that the food security program is one of the prioritised components of the Village Fund, annually budgeted through village planning documents and implemented through both physical infrastructure development and community empowerment initiatives. The Chi-square test (α = 0.05) indicates a statistically significant relationship between the program’s implementation and community perceptions of SDG 2 achievement (χ² = 20.241 > χ²table = 9.488). It can be concluded that the implementation of the village fund programme for food security is positively associated with community perceptions of achieving Village SDG 2. Communities that have benefited—either directly or indirectly—from the programme tend to perceive better progress toward SDG 2, while those who have not experienced the benefits tend to perceive lower levels of achievement.